PSIKOLOGI TOKOH DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY - Umilia, Umilia; Effendy, Chairil; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe general problem of this research was the analysis of psychology figures in the Novel of Bidadari Bermata Bening by Habiburrahman El Shirazy. Novel Bidadari Bermata Bening tells about the pesantren world and two young people who are trapped in love, at the first time they just amazed each other but it turn into love that unequaled. Tha research questions are: (1) main character thought, (2) behavior of main character, (3) additional character thought, (4) additional character behavior, (5) the implementation plant at school. The purpose of this research is to describe the aspect of thought and behavior of the main character as well as additional characters. This research used the descriptive method in the form of qualitative research. The data is the novel texts with data in the form of quotations that indicate the existence of the main characters, the behavior of additional characters. The technique used in this research was documenter study, and the tool of data collection was the researcher herself as the key instrument. Based on the results of data analysis, 7 data the main character?s thought, 11 data major dexterity behavior, 3 data additional character?s thiughts, and 27 data the behavior of additional characters.Keywords: psychology, figures, Bidadari Bermata Bening.